Employment, working conditions, and preterm birth: results from the Europop case-control survey. Issue 5 (13th April 2004) - Saurel-Cubizolles, M J; Zeitlin, J; Lelong, N; Papiernik, E; Di Renzo, G C; Bréart, G
Abstract : Study objective: To analyse the relation between preterm birth and working conditions in Europe using common measures of exposure and to test whether employment related risks varied by country of residence. Design: A case-control study in which cases included all consecutive singleton preterm births and controls included one of every ten singleton term births in each participating maternity unit. Data about working conditions were obtained by interview from women after delivery. Setting: Sixteen European countries. Participants: The analysis included 5145 preterm and 7911 term births of which 2369 preterm and 4098 term births were to women employed during pregnancy. Analyses of working conditions were carried out for women working through at least the third month of pregnancy. Main results: Employed women did not have an excess risk of preterm birth. Among working women, a moderate excess risk was observed for women working more than 42 hours a week (OR = 1.33, CI = 1.1 to 1.6), standing more than six hours a day (OR = 1.26, CI = 1.1 to 1.5), and for women with low job satisfaction (OR = 1.27, CI = 1.1 to 1.5). There were stronger links in countries with a lower overall level of perinatal health and a common practice of long prenatal leaves. Conclusion: These findings show that specific working conditions affect the risk of preterm birth. They also suggest employment related risks could be mediated by the social and legislative context.